Predicting Risk Factors of Working Aged Hemorrhagic Stroke Patients in a Tertiary Teaching Hospital in Chiang Mai - Suphannee Triamvisit; Wilaiwan Chongruksut; Wanarak Watcharasaksilp; Rujee Rattanasathien (JMIR Publications, 2018)
Stroke is the third leading cause of morbidity and mortality in Thailand accounting for a significant and increasing share of hospital costs. The purpose of this project is to study the epidemiology of the prevalence and its predicting factors of working aged hemorrhagic stroke (HS) patients admitted at a tertiary teaching hospital in Chiang Mai, Thailand. We conducted a five-year retrospective descriptive study. The subjects in this study were patients diagnosed with HS, between 15-59 years of age, and admitted to a tertiary teaching hospital in Chiang Mai, Thailand from January 2009 to December 2013. A total of 404 working aged adults who had HS were admitted to the hospital during this review period; 60.9% males and 39.1% females. Nearly 70% of patients were between 46-59 years of age (M = 47.5, SD = 9.8). Of the patients admitted to the hospital, 76.7% were transferred there from other hospitals. Intracerebral hemorrhage was present in 59.7% of patients. Severe HS occurred in 35.9% of the patients with a Glasgow Coma Score from 3-8. Approximately 69% of the working aged HS patients required surgery. The top five identified risk factors for HS were hypertension (83.4%), hyperlipidemia (38.9%), alcohol consumption (21.5%), smoking (15.3 %), and drug non-adherence (14.9%). We found significantly associated risk factors in working-aged HS by multivariate analysis among male gender (p < .001), drug non-adherence (p = .047), and hypertension (p = .048). Raising awareness to reduce risk behavior and health promotion in the community are the keynotes for health care providers in working-aged HS prevention.